Bridging Cultures through Language: Examining the Linguistic and Cultural Experiences of IISMA Awardees - Wicaksono, Julien Arief; Rinda, Renata Kenanga; Indrastana, Nodistya Septian; Rahmanita, Meiga; Rachman, Nur Afni; Suharsono, Degita Danur (P3M Politeknik Negeri Jember, 2024)
This study explores the pivotal role of language in fostering cross-cultural appreciation among Indonesian International Student Mobility Awards (IISMA) awardees. We examined the experiences of two awardees of prestigious international exchange programs to understand how language acquisition and use influenced their cultural perceptions and interactions. Using a mixed-methods approach, we conducted in-depth interviews and administered surveys to gather data on the participants’ language learning journeys, intercultural communications, and shifts in cultural perspectives. The selected participants represented diverse linguistic and cultural backgrounds and completed exchanges in countries where they needed to navigate a foreign language. Our findings reveal that language proficiency significantly enhanced the awardees’ ability to appreciate and engage with host cultures. Key themes emerged, including: 1) the role of language as a gateway to deeper cultural understanding; 2) Challenges and breakthroughs in intercultural communication; 3) The impact of idiomatic expressions on cultural insight; 4) Changes in self-perception and cultural identity through language learning; and 5) The development of empathy and cultural relativism. Quantitative data indicated a strong positive correlation between language proficiency and measures of cultural appreciation. Qualitative analysis provided rich insights into the nuanced ways language shaped the awardees’ cross-cultural experiences. This research contributes to our understanding of the intricate relationship between language and culture in international education contexts. It offers valuable implications for enhancing student exchange programs and promoting global citizenship through targeted language and cultural learning strategies.